ANALYZING AN EFL TEACHER'S CLASSROOM MANAGEMENT IN A PRIVATE JUNIOR HIGH SCHOOL IN BANDUNG - Imas Suparsih, - (2018)
The problem face by the EFL students is the fact that they have limited time to use English in their daily life. Meanwhile, the classroom is the one environment in which they can practice their language. This study is aimed at figuring out an EFL teacher's classroom management styles and the students' responses toward the classroom management styles applied in teaching and learning process. This study was conducted under the qualitative case study design. The case involved an EFL teacher and 31 students. The data were gathered from classroom observations, questionnaires, and interviews. Based on the findings, the teacher dominantly used authoritative classroom management style followed by authoritarian, then laissez-fair and indifferent classroom management styles. The teacher did the activities such as managing time, managing seating arrangement, establishing rules, providing feedback, giving rewards, managing individual, pair and group work, and monitoring students' activities. Moreover, the students presented positive response toward the teacher classroom management styles. The students tend to listen and act out based on what the teacher suggested or instructed. The results are expected to raise the EFL teachers' awareness that managing classroom is valuable and using more than one classroom management styles is possible. Further research with more representative respondents is recommended. ---- Permasalahan yang dihadapi oleh siswa EFL adalah mereka memiliki waktu yang terbatas untuk menggunakan Bahasa inggris dalah kehidupan sehari-hari. Sedangkan, kelas adalah lingkungan dimana mereka bisa mempraktekan Bahasa Inggris. Tujuan dari penelitian ini untuk memberikan gambaran bagaimana style guru dalam mengatasi kelas dan untuk mengetahui respon siswa terhadap style guru ketika pembelajaran berlangsung. Penelitian ini menggunakan kualitative case study dengan satu guru dan 31 siswa sebagai respondent. Observasi, kuesioner dan interview adalah intruments yang digunakan untuk mengumpulkan data. Hasil dari penelitian menunjukan authoritative merupakan style yang dominant digunakan oleh guru diikuti authoritative, laissez-fair dan indifferent styles. Guru menerapkan aktifitas seperti mengatur waktu, mengatur posisi duduk siswa, memberikan peraturan, memberikan feedback, memberrikan rewards, mengatur pekerjaan siswa baik individual, pair dan kelompok, dan memantau aktifitas siswa selama pembelajaran berlangsung. Siswa menunjukan respon yang positif terhadap style guru dalam mengatasi kelas. Siswa cendenrung mendengarkan dan mematuhi apa yang diperintahkan oleh guru. Hasil dari penelitian ini diharapkan dapat meningkatkan kepedulian guru akan pentingnya mengatasi kelas dan guru juga memungkinkan menggunakan lebih dari satu style dalam mengatasi kelas. Untuk peneliti yang berminat dibidang yang sama dengan disarankan untuk meneliti dengan respondent yang lebih banyak.